Discovery and development of safe-in-man broad-spectrum antiviral agents. (April 2020) - Andersen, Petter I.; Ianevski, Aleksandr; Lysvand, Hilde; Vitkauskiene, Astra; Oksenych, Valentyn; Bjørås, Magnar; Telling, Kaidi; Lutsar, Irja; Dumpis, Uga; Irie, Yasuhiko; Tenson, Tanel; Kantele, Anu; et al.
Highlights: We reviewed the discovery and development process of broad-spectrum antiviral agents. We summarized the information on 120 safe-in-man agents in a freely accessible database. Further studies will increase the number of broad-spectrum antivirals, expand the spectrum of their indications, and identify drug combinations for treatment of emerging and re-emerging viral infections. Abstract: Viral diseases are one of the leading causes of morbidity and mortality in the world. Virus-specific vaccines and antiviral drugs are the most powerful tools to combat viral diseases. However, broad-spectrum antiviral agents (BSAAs, i.e. compounds targeting viruses belonging to two or more viral families) could provide additional protection of the general population from emerging and re-emerging viral diseases, reinforcing the arsenal of available antiviral options. Here, we review discovery and development of BSAAs and summarize the information on 120 safe-in-man agents in a freely accessible database (https://drugvirus.info/ ). Future and ongoing pre-clinical and clinical studies will increase the number of BSAAs, expand the spectrum of their indications, and identify drug combinations for treatment of emerging and re-emerging viral infections as well as co-infections.